Магнiтно модифiкованi електроспінінгові нановолокна для гiпертермiї - Molcan, M.; Safarik, I.; Pospiskova, K.; Paulovicova, K.; Timko, M.; Kopcansky, P.; Torma, N. (Publishing house "Academperiodika", 2020)
Several methodologies for the preparation of nanofibrous materials exist. Electrospinning is currently the most popular technique due to its versatility and simplicity. Nanofibrous materials prepared in such a way are widely studied in medicine and material engineering. Polyvinyl butyral (PVB) nanofibers were generated by a rod-shaped spinning-electrode. Nanofibers were modified by a magnetic fluid (MF) added into the PVB solution. These magnetic nanofibers can be considered as a material for magnetic hyperthermia applications, either as implants or for the surface heating. The samples with various magnetic particle concentrations were tested in the alternating magnetic field. An immediate increase in the temperature after the field application was observed. The nature of the temperature rise is interesting: a non-linear increase could be seen, which is in contrast to the rising temperature for pure magnetic fluids.